A perspective of lipid nanoparticles for RNA delivery - Yutian Ma; Shiyao Li; Xin Lin; Yupeng Chen (Exploration)
Abstract Over the last two decades, lipid nanoparticles (LNPs) have evolved as an effective biocompatible and biodegradable RNA delivery platform in the fields of nanomedicine, biotechnology, and drug delivery. They are novel bionanomaterials that can be used to encapsulate a wide range of biomolecules, such as mRNA, as demonstrated by the current successes of COVID‐19 mRNA vaccines. Therefore, it is important to provide a perspective on LNPs for RNA delivery, which further offers useful guidance for researchers who want to work in the RNA‐based LNP field. This perspective first summarizes the approaches for the preparation of LNPs, followed by the introduction of the key characterization parameters. Then, the in vitro cell experiments to study LNP performance, including cell selection, cell viability, cellular association/uptake, endosomal escape, and their efficacy, were summarized. Finally, the in vivo animal experiments in the aspects of animal selection, administration, dosing and safety, and their therapeutic efficacy were discussed. The authors hope this perspective can offer valuable guidance to researchers who enter the field of RNA‐based LNPs and help them understand the crucial parameters that RNA‐based LNPs demand.